Soil-Structure Interaction, Underground Structures and Retaining Walls: Proceedings of the ISSMGE Technical Committee 207 International Conference on Geotechnical Engineering - Ulitsky, V. M; Shashkin, Alexey G (SAGE Publications, Limited, 2015)
With construction techniques becoming ever more complex, and population pressure leading to the development of increasingly problematic sites, expertise in the area of soil structure interaction is crucial to architectural and construction industries worldwide.This book contains the proceedings of the ISSMGE Technical Committee 207 International.